First record of synthetic micro-fibre ingestion by Mute Swans Cygnus olor and Whooper Swans C. cygnus - Coughlan, Neil E.; Lyne, Linda; Kelly, Thomas C.; Johnston, Ryan; Holmes, Craig; Griffith, Rose M.; Dick, Jaimie T.A.; Brides, Kane; Baker-Arney, Connie; Cunningham, Eoghan M. (Wildfowl, 2021)
Despite an acute focus on the ingestion of large and small synthetic debris by seabirds, scant consideration has been given to their occurrence in other avian species inhabiting coastal and inland wetland areas. Here, we assess ingestion of synthetic micro-fibres (i.e. microplastics and other non-natural fibres, 0.5–5 mm in size) by Mute Swans Cygnus olor inhabiting a large freshwater reservoir (n = 12 faecal samples), and from Whooper Swans C. cygnus wintering on a remote offshore Atlantic island (n = 11 faecal samples). Samples were chemically digested to eliminate labile organic matter including natural fibres. In total, 79 synthetic micro-fibres were recovered at frequencies of 4.2 ± 0.8 and 2.6 ± 0.7 (mean ± s.e.) per sample, ranging from 0–10 and 0–7 micro-fibres per sample, for Mute Swan and Whooper Swan faecal samples, respectively. The number of synthetic micro-fibres recovered did not differ significantly between species or sites. Similarly, there was no difference in the number of synthetic micro-fibres detected per gram of faecal sample. Overall, our preliminary data further bolster emerging records for the ingestion of synthetic debris by non-marine waterbirds inhabiting freshwater and coastal areas.